The Relationship Between Stress Levels With The Incidence Of Hypertension In Menopausal Women - Huda Rohmawati; Siti Aminah; Sunaningsih; Rony D.; Wismoadi A. (Journal of Global Research in Public Health, 2021)
Background: Menopause is the cessation of the last menstruation that occurs in the climacteric period and the hormone estrogen is no longer formed. The older the age, the more diseases suffered at the age of menopause, such as hypertension. Hypertension is a condition when a person experiences an increase in blood pressure either slowly or suddenly. The factors that cause hypertension are mostly due to stress. This study aims to determine the relationship between stress levels with the incidence of hypertension in postmenopausal women. Methods: The design of this research is correlational analytic. The sample is 50 respondents with the Stratified Random Sampling technique. The instrument used is a questionnaire. The results of the study were analyzed using the Spearman rank statistical test. Result: The results showed that there were 24 people (48.0%) with moderate stress levels and 18 people (36.0%) experiencing Stage I Hypertension. The results of the Spearman's Rank correlation test showed that the value of value = 0.000 was smaller than the value of = 0.05 so that H0 is rejected and H1 is accepted, meaning that there is a relationship between stress levels and the incidence of hypertension in postmenopausal women. Conclusion: It is expected that respondents will increase their knowledge about how to deal with stress so that they do not experience stress at a severe level so that it does not have a bad impact on them.